Mewujudkan Kemandirian Desa dengan Pemanfaatan dan Pencegahan Peyalahgunaan Dana Desa - Lalu Satria Utama; Ainur Rofiq Putra Mudho (Jurnal Perlindungan Masyarakat: Bestuur Praesidium, 2024)
This article analyzes or discusses realizing good governance in Indonesia by creating village independence through the use of village funds or other village income. This article uses the method of writing a literature study or literature study based on related sources and relevant previous research. Good governance in general is something agreed upon by various parties, especially the government, in the process of implementing good and responsible government. Good village governance is very important to create effective and efficient village government, improve public services, and of course improve the welfare of village communities and other things. Building villages towards independence so that they are competitive, infrastructure development, progress in the economic, social and cultural fields can only occur with good village management. By utilizing existing village funds and of course with the results of existing village income such as BUMDes and so on, is one way that can realize the village independence that has been aspired to. However, there is not much abuse or misappropriation of village funds or income from the village by responsible parties, of course this is a problem that must be resolved so that the implementation of independent villages can run properly and can be realized in various regions throughout Indonesia.